Knowledge and Attitude Towards Orthodontic Treatment among High School Students of Biratnagar - Acharya, Anand; Giri, Nidhi; Niroula, Shreya; Bhagat, Tarakant (Orthodontic Journal of Nepal, 2025)
Introduction: Orthodontic treatment aims to improve esthetics, function, and the structural balance of the stomatognathic system, thereby enhancing the self-esteem of the patients. This study was conducted with the aim of assessing the orthodontic treatment knowledge and attitude among high school students of Biratnagar. Materials and Methods: This was a descriptive, cross-sectional, questionnaire-based study carried out among 1,111 high school students. The questionnaire included 14 closed-ended questions assessing orthodontic knowledge and 10 closed-ended questions for assessing orthodontic attitude. The mean knowledge and attitude were calculated and compared between the students from government and private schools. Results: The mean knowledge scores for private and government school students were 8.68 and 9.05, respectively. The mean attitude scores were 4.63 for private school students and 4.58 for government school students. A statistically significant difference (p<0.001) was observed in knowledge scores between the two groups, with government school students demonstrating a higher mean rank (587.3) compared to private school students (448.7). However, no significant differences were noted between them when orthodontic attitude were assessed (p = 0.592). Conclusion: Government school students had significantly higher orthodontic knowledge as compared to the private school students; however, no significant difference was found in orthodontic attitude between the groups.